Template-assisted synthesis of 2D heterostructure photocatalysts - Sun, Jiajun (Nanyang Technological University, 2024)
Two-dimensional (2D) heterostructures, characterized by their extensive interfacial area, hold remarkable potential as exceptionally efficient photocatalysts. In this thesis, microscale uniform 2D heterostructures with designed thickness and structure as well as controlled surfaces can be prepared via template-assisted bottom-up or top-down fabrication. The magnetic attributes of Fe3O4 templates provide notable advantages, making it possible to easily separate the resulting 2D heterostructures from other components in the solution using magnetic forces.